Dzisiejsza obecność teologa i teologii we wspólnocie akademickiej - Moskałyk, Jarosław (Poznańskie Studia Teologiczne, 2020)
The presence of theology in the academic community is today a challenge of particular significance. One of the most important reasons are political transformations in the post-communist countries of Europe in the last 25 years, as well as ideological and axiological transformations in the West of our continent. All these processes have affected many spheres of social, cultural and spiritual life and are directly related to shaping the contemporary theological thought. Although theology acquires potentially new opportunities for development and impact in the university space, in practice there are increasing difficulties in its affirmation. The problem primarily concerns the scientific profile of theology and the responsibility of theologians themselves.